Evaluasi Kelayakan Tahanan Isolasi Instalasi Listrik pada Rumah Tinggal dengan Usia Penggunaan 50 Tahun - M. Syekhurohim; Aripin Triyanto; Budiman (CV. Multi Kreasi Media, 2025)
Electrical installations used for more than 50 years often experience a decline in quality and pose various safety risks, such as fires, electric shocks, and damage to electrical equipment. This study aims to analyze the feasibility of electrical installations in residential homes that have been used for more than 50 years, as well as determine the need for revitalization to improve the safety and reliability of the electrical system. The research method was conducted through a quantitative approach with field surveys and technical measurements. Insulation resistance measurements were performed to assess the quality of cable insulation. The collected data includes the physical condition of cables, connectors, protective components, grounding systems, and electrical load distribution. The measurement results before revitalization showed that the insulation resistance values varied between 0.5 MΩ to 0.9 MΩ, all of which were below the minimum feasibility standard of 1 MΩ according to PUIL 2011. After revitalization, the measurement results showed a significant increase with insulation resistance values reaching 2.0 MΩ to 2.5 MΩ, ensuring that all rooms now meet the minimum feasibility standards. These findings emphasize the importance of revitalization to extend the lifespan of electrical installations and reduce safety risks. This research provides practical recommendations for homeowners and electrical technicians to conduct regular inspections and revitalization of aging electrical installations to ensure the safety and efficiency of the electrical system.